Re: Differential equation

Maybe you are correct, at this step $\displaystyle -e^{-y} = e^x + C$ , multiply both sides through by $\displaystyle e^{y} $

What do you get?

Re: Differential equation

Quote:

Originally Posted by

**M.R** $\displaystyle ln(e^{-y^{-1})} = ln(e^x + C)$

$\displaystyle \frac{-1}{y} = x + ln(C)$

This is not right.

ln(ab) = ln(a) + ln(b)

ln(a + b) ≠ ln(a) + ln(b)

Quote:

Originally Posted by

**M.R** $\displaystyle -e^{-y} = e^x + C$

You already had this.

What do you get if you multiply left and right with $\displaystyle e^y$?

Re: Differential equation